A Method for Formulating a Manufacturing Strategy Using Fuzzy Dematel and Fuzzy Vikor - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L (Taylor and Francis Ltd., 2024)
The purpose of this paper is to propose a quantitative method for formulating a manufacturing strategy. It is based on the accepted framework for manufacturing strategy formation containing competitive priorities and manufacturing decisions. The existing literature shows a limited number of papers using quantitative methods for modeling the framework. The proposed method utilizes a combination of three multi-criteria decision making methods (MCDM) to formulate the strategy. They are the fuzzy version of DEMATEL, VIKOR, and AHP. The proposed method supports managers in generating action plans for manufacturing that are aligned with the company’s overall strategy. It also produces a ranking of the plans, so managers can focus on those that are most important for achieving the company’s goals. The contribution of the proposed method is that it captures the priorities and the complex relationships among the factors affecting the manufacturing strategy. From a practical point of view, its value is the support provided for managers in formulating manufacture. It was applied in one company, where managers stated that they found the resulting strategy useful in terms of supporting the company’s objectives. © 2023 American Society for Engineering Management.